2015
DOI: 10.1161/jaha.115.001914
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Therapy Reversibly Increases Endothelium‐Dependent Vasodilation in Men With Prostate Cancer

Abstract: BackgroundAndrogen deprivation therapy (ADT) is a standard treatment for patients with aggressive prostate cancer. Although ADT improves survival, it increases the risk of diabetes. Emerging evidence suggests that ADT increases adverse cardiovascular events as early as 3 months after initiation in patients with cardiovascular disease, but the mechanism is unknown. We hypothesized that ADT may impair endothelium‐dependent vasodilation due to increases in lipids and insulin resistance and may provide a link for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…No clear effect of ADT on blood pressure has been delineated. Indeed, counterintuitively, ADT improved vascular endothelial function leaving the mechanism of atherogenesis unclear 7 . The effects of ADT on various CV risk parameters are summarized in Table 2.…”
Section: Effects and Pathophysiology Of Adt On The CV Systemmentioning
confidence: 99%
“…No clear effect of ADT on blood pressure has been delineated. Indeed, counterintuitively, ADT improved vascular endothelial function leaving the mechanism of atherogenesis unclear 7 . The effects of ADT on various CV risk parameters are summarized in Table 2.…”
Section: Effects and Pathophysiology Of Adt On The CV Systemmentioning
confidence: 99%
“…It has been proposed that this effect is mediated by the opening of calciumdependent potassium channels and the closure of calcium channels [Perusquia and Villalon, 1999;Deenadayalu et al 2001Deenadayalu et al , 2012Ding and Stallone, 2001;Oloyo et al 2011]. Paradoxically, another recent study found ADT administration to promote vasodilation [Nguyen et al 2015b].…”
Section: Direct Hormonal Effects On Atherosclerotic Plaque Stability mentioning
confidence: 99%
“…167,168 Moreover, the changes in metabolism and vascular function return to baseline on ADT cessation. 169…”
Section: Metabolic Complications Of Cancer Therapiesmentioning
confidence: 99%